2013
DOI: 10.9745/ghsp-d-13-00037
|View full text |Cite
|
Sign up to set email alerts
|

Limited electricity access in health facilities of sub-Saharan Africa: a systematic review of data on electricity access, sources, and reliability

Abstract: Only 34% of hospitals have reliable electricity access in surveyed sub-Saharan African countries. However, analysis in 2 countries indicates modest improvements in electricity access over time. Ambitious plans to improve health service delivery in sub-Saharan Africa need to address this critical issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(127 citation statements)
references
References 2 publications
4
123
0
Order By: Relevance
“…The importance of an enabling environment in order for health workers to deliver good-quality care has been emphasised previously (Maclean 2003). Although the United Nations' fifth Millennium Development Goal (MDG) era promoted access to health facilities and skilled birth attendance, basic infrastructure and logistics management at health facilities remain a challenge in several settings (Adair-Rohani 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The importance of an enabling environment in order for health workers to deliver good-quality care has been emphasised previously (Maclean 2003). Although the United Nations' fifth Millennium Development Goal (MDG) era promoted access to health facilities and skilled birth attendance, basic infrastructure and logistics management at health facilities remain a challenge in several settings (Adair-Rohani 2013). …”
Section: Discussionmentioning
confidence: 99%
“…A review of healthcare facilities in several sub-Saharan countries showed that, on average, 26% of the facilities examined had no access to electricity; 28% had reliable access to electricity, and 7% relied solely on generators. 54 WHO has proposed a multi-tier metric for assessing access to electricity in health-care facilities, and this metric includes peak power capacity, daily energy capacity, duration of supply, evening peak hours supply, aff ordability, quality, reliability, operational sustainability, environmental sustainability, and environmental health. 55 This metric has yet to be operationalised, but the Lancet Countdown will draw on this measure for reporting on energy access in the health-care sector where feasible.…”
Section: 4: Energy Access For Health Facilitiesmentioning
confidence: 99%
“…Ventilators and other equipment in the operating theater and ICU at the hospital, when available, are often older, outdated, or have been donated and no longer work due to inability to obtain parts, inappropriate design for an environment with erratic power supplies, and lack of biomedical engineering training and maintenance [6,8,9,39,40]. Oxygen supply is variable and challenging and is provided by oxygen concentrators that are expensive but easy to maintain [6,8,36].…”
Section: Support Servicesmentioning
confidence: 99%
“…Only 34% of hospitals in SubSaharan Africa that are electrified have a reliable electricity source [40], and only 22% of hospitals in Tanzania have been shown to have the basic infrastructure necessary to provide emergency and surgical care [24]. The lack of a reliable electricity supply is even more urgent when oxygen concentrators are in use and power surges can damage monitoring equipment and ventilators.…”
Section: Infrastructurementioning
confidence: 99%